Risk-based capital requirements for mortgage loans - Calem, Paul S.; LaCour-Little, Michael (Journal of Banking & Finance, 2004)
We contribute to the debate over the reform of the Basel Accord by developing risk-based capital requirements for mortgage loans held in portfolio by financial intermediaries. Our approach employs simulation of both economic variables that affect default incidence and conditional loss probability distributions. Results indicate that appropriate capital charges for credit risk vary substantially with loan characteristics and portfolio geographic diversification. Hence, rules that offer little risk differentiation, including the current Basel I regime and “standardized” approach proposed in Basel II result in significant divergence between regulatory and economic capital. These results highlight the incentive problems inherent in simplified methods of capital regulation.